Electronic community health information system practice and associated factors among health extension workers in South Wollo Zone, North East Ethiopia: Mixed study - Mohammed Ali Dawud; Mulugeta Hayelom Kalayou; Yitbarek Wasihun; Toyeb Yasine; Tewoflos Ayalew; Mulugeta Desalegn Kasaye (Computer Methods and Programs in Biomedicine Update, 2025)
Background: Despite several hindering factors, such as limited internet access, unstable power supply, insufficient smart phone, lack of trainings regarding e-CHIS, affecting its implementation, electronic community health information system is a digitized type of community health information system content on a mobile platform that creates a logically interconnected programmatic content module for usage by health extension workers to register and provide high quality health services across the Nation. This study assessed electronic community health information system practice and its associated factors among health extension workers of south Wollo zone, Amhara, Ethiopia, 2024. Methods: A facility-based cross-sectional study was conducted from 22 January 2024 to 01 April 2024. Study participants were selected by using simple random sampling for the quantitative study, and purposive sampling was employed for qualitative study. Data were collected using an interviewer-administered questionnaire. Data were entered into Epi Data version 4.6.1 and exported to SPSS version 26 for analysis. Descriptive statistics were summarized using figures and tables. Both bi-variable and multivariable logistic regression analyses were carried out. The level of significance was determined based on the AOR with 95 % CI and P-value at <0.05. Thematic analysis was used to analyze the data for qualitative part. Results: In this study, 46 % of health extension workers showed Good practice of eCHIS. Respondents’ Knowledge, presence of electricity at the health facility, Availability of tablets for eCHIS, and work experience of participants were statistically significant associations with the practice of eCHIS. Conclusion and Recommendation: In this study, the practice of eCHIS was 46 %. Variables such as availability of tablets, work experience, knowledge, and facility electricity supply were factors associated with electronic-health-information-system. Improving the knowledge of the participants would improve the e-CHIS practice.